Study of Kurt Dietrich’s Design Principles and Elements in Batak Karo - Roosandriantini, Josephine; Prijotomo, Josef (Jurnal Koridor, 2024)
Architectural design is the process to create a building that aims for the comfort and beauty of the building itself. An architect in creating or designing a building cannot be separated from the use of design principles in his design, in order to create aesthetics in his architectural works. This study aims to show that design elements and principles which are a European mindset can show that Indonesian architecture also has design principles such as modern, classic, and contemporary architecture. With this awareness in mind, research on Archipelago architecture should be carried out critically so that the European knowledge taken is the knowledge that has been able to conform with the Archipelago mindset, not with the European mindset. This research can be useful for providing knowledge or insight into proving a European design principle (mindset) that can also be applied to objects of archipelago architecture. Explorative research method with a qualitative approach. European-minded design principles to recognize the existence of Batak Karo architecture. The analysis is carried out by ensuring that Kurt Dietrich's principles are based on the European mindset of the Karo Batak, which results in non-European design principles. The test was carried out to discuss whether there were design principles that applied to the Karo Batak, it was found that exclusive design principles were a unified archipelago design principle, and had the peculiarities of each architecture as well as diversity in archipelago architecture.